The Condition of Significant Wave Height and Wind Velocity in Makassar Strait during 2017 - Hanah Khoirunnisa; Shofia Karima (Politeknik Negeri Batam, 2019)
This study aims to look at the conditions and characteristics of significant wave height and its relationship to wind velocity in the Makassar Strait in 2017. The data used in this study are bathymetry data from GEBCO with a resolution of 30 seconds, significant wave height data (Hs) with a resolution of 0.25 x 0.25 as well as wind velocity and direction with a resolution of 0.25 x 0.25 which are secondary data results from the European Center for Medium-Range Weather Forecasts (ECMWF) with a span of one year in 2017. The method used in this research is an analysis of the energy spectrum of significant wave height using Fast Fourier Transform. In addition, wind velocity and direction are processed by using GrADS software to see the visual conditions. Based on this study, it can be concluded that wind velocity is strongly associated with significant wave height values. This can be seen at each sample point in the Makassar Strait, where when the value of wind velocity is high, the value of significant wave height has the same conditions, and vice versa. The wind velocity value has a maximum value in the Makassar Strait during the east season with a value of more than 4.5 m/s. The highest energy spectrum occurs at point 3 in the Makassar Strait, which is 7303 m2 with a period of 6 months.